A comparison of methods of analysing exercise tests for diagnosis of coronary artery disease. Issue 6 (December 1989) - Deckers, J W; Rensing, B J; Tijssen, J G; Vinke, R V; Azar, A J; Simoons, M L
Abstract : The diagnostic accuracy of the following methods of analysing exercise tests were evaluated: (a) the cumulative area of ST segment depression during exercise normalised for workload and heart rate (exercise score); (b) discriminant analysis of electrocardiographic exercise variables, workload, and symptoms; and (c) ST segment amplitude changes during exercise adjusted for heart rate. Three hundred and forty five men without a history of myocardial infarction were studied. One hundred and twenty three were apparently healthy. Less than half (170) had coronary artery disease. All had a normal electrocardiogram at rest. A Frank lead electrocardiogram was computer processed during symptom limited bicycle ergometry. The accuracy of the exercise score (a) was low (sensitivity 67%, specificity 90%). Discriminant analysis (b) and ST segment amplitude changes adjusted for heart rate (c) had excellent diagnostic characteristics (sensitivity 80%, specificity 90%), which were little affected by concomitant use of beta blockers. Both methods seem well suited for diagnostic application in clinical practice.